ANALISIS KONDISI RIIL PERSEDIAAN DOSEN PADA POLITEKNIK NEGERI MANADO - Selfy Manueke; Meiske W Manopo; Iyam L Dua (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2022)
Manado State Polytechnic is one of the higher education institutions under the Ministryof Education, Culture, Research and Technology which currently provides vocationaleducation with 6 (six) different fields of knowledge, namely Civil Engineering, ElectricalEngineering, Mechanical Engineering, Accounting, Business Administration andTourism. . In organizing educational activities, lecturers are one of the resources thatmust be considered because without lecturers, educational activities at the Polytechniccannot be held. Based on initial observations, the current condition of lecturers asprofessional educators at this institution will experience a decline in the number within10 years because most lecturers retire during that time. The purpose of this study is toanalyze the real condition of the supply of permanent lecturers at the Manado StatePolytechnic so that this institution can recruit and select lecturers according to the needsof each department. The method used is a qualitative method through interviews anddocument analysis to obtain information about the real condition of the supply oflecturers at the Manado State Polytechnic. The result achieved is an empirical analysisof the supply of lecturers in each department at the Manado State Polytechnic. It wasfound in this study that in the next 10 years period, 133 (46.83%) Manado StatePolytechnic lecturers will retire, namely lecturers who are in the age range of 55-60 yearsand > 60 years.Therefore, the management of Manado State Polytechnic has to anticipateand plan its new recruitment and selection of lecturers in order to maintain the quality ofits education.